Perbaikan Metode Kerja untuk Meningkatkan Line Efficiency dengan Konsep ECRS - Pertiwi, Asariella Findya Octa; Astuti, Rahmaniyah Dwi; Asariella Findya Octa Pertiwi; Rahmaniyah Dwi Astuti (Universitas Serang Raya, 2020)
The Assembly line is the assembly process that is carried out based on the order of the production process in the production line. The problem that is often found in assembly lines is bottleneck conditions where some material piled up at the station. This situation indicates an imbalance in the production line. The improvement of the work method is one of the effective ways that can increase line efficiency. This study presents an increase in line efficiency by improving working methods in a washing machine assembly line of PT.X. The study aimed to increase the value of line efficiency by improving work methods. In this study, improvements were made using the line balancing method and Eliminate, Combine, Rearrange, Simplify (ECRS) concept. The results that have been done, the obtained value of line efficiency for washing machine products is 76.76%. This value has not reached the company's productivity target of 99.50%. Therefore it is necessary to improve the assembling line to increase the value of product production. The proposed improvements made with improvements to the work methods on the assembling line obtained 89.38% results is to increase the amount of line efficiency by improving work methods.